Diagnosis and detection of bone fracture in radiographic images using deep learning approaches - Aldhyani, Theyazn; Ahmed, Zeyad A. T.; Alsharbi, Bayan M.; Ahmad, Sultan; Al-Adhaileh, Mosleh Hmoud; Kamal, Ahmed Hassan; Almaiah, Mohammed; Nazeer, Jabeen (Frontiers in Medicine, 2025)
Bones are a fundamental component of human anatomy, enabling movement and support. Bone fractures are prevalent in the human body, and their accurate diagnosis is crucial in medical practice. In response to this challenge, researchers have turned to deeplearning (DL) algorithms. Recent advancements in sophisticated DL methodologies have helped overcome existing issues in fracture detection. Nevertheless, it is essential to develop an automated approach for identifying fractures using the multi-region X-ray dataset from Kaggle, which contains a comprehensive collection of 10,580 radiographic images. This study advocates for the use of DL techniques, including VGG16, ResNet152V2, and DenseNet201, for the detection and diagnosis of bone fractures. The experimental findings demonstrate that the proposed approach accurately identifies and classifies various types of fractures. Our system, incorporating DenseNet201 and VGG16, achieved an accuracy rate of 97% during the validation phase. By addressing these challenges, we can further improve DL models for fracture detection. This article tackles the limitations of existing methods for fracture .detection and diagnosis and proposes a system that improves accuracy. The findings lay the foundation for future improvements to radiographic systems used in bone fracture diagnosis.